Management tools in the management of human university talent (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2018)
The purpose of this essay is aimed at reflecting on management tools in the management of university human talent. The methodology used responds to a review of the theoretical aspects that explain the implications of the constructs related to an academic vision for training management that consolidates professional competences from a psychological, social and work perspective. The university management is oriented towards search and maintenance of excellence and quality in its different levels and modalities. The purpose is to achieve a quality teaching and learning process in professional training. Currently there are contributions from various disciplines that contribute to organizational management such as NLP, motivation, emotional intelligence and effective communication, among others, contribute to the development of psychosocial and organizational skills. The term management of human talent presents diverse connotations, among them the development of intellectual, emotional and labor competences. It was concluded that the use of management tools in professional training, leads to human, citizen and professional development, in such a way, to converge from a collective consciousness with intellectual potential, knowledge, labor skills to improve their quality of life, trying to give effective and timely responses to the problems that contemporary society faces.
Keywords: university management; human talent management; psychosocial and organizational, management tools